Respuesta :
Answer:
We have
k^2 - 25f^2 + 5kf - 25f^2 =
k^2 - (5f)^2 + 5f( k - 5f) =
( k - 5f )( k + 5f ) + 5f( k - 5f ) =
( k - 5f )( k + 5f + 5f ) =
( k - 5f )( k + 10f );
Step-by-step explanation:
Answer: The required factored form of the given expression is [tex](k-5f)(k+10f).[/tex]
Step-by-step explanation: We are given to factor the following quadratic expression :
[tex]E=k^2+5kf-50f^2~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
To factor the given expression, we need two integers with sum 5 and product -50 and those two integers are 10 and -5.
The factorization of expression (i) is as follows :
[tex]E\\\\=k^2+5kf-50f^2\\\\=k^2+10kf-5kf-50f^2\\\\=k(k+10f)-5f(k+10f)\\\\=(k-5f)(k+10f).[/tex]
Thus, the required factored form of the given expression is [tex](k-5f)(k+10f).[/tex]